A dialectical conception of art derived from the genesis of the concept of work in Hegel's Phenomenology of Spirit - Márcia Gonçalves; Pedro Rocha de Oliveira (Kriterion, 2006)
Hegel's philosophy of art is not specifically deployed in his Phenomenology of Spirit. However, it is possible to understand the systematic relationship between many fundamental concepts of this 1807 book and Hegel's mature concept of art. Based on this relationship, three distinct but complementary theses will be advanced: 1. Of the artwork as ideal product of the work of the spirit (Geist); 2. Of the symbolism of natural religion as the product of the craftsman's work, as implying a transition to the beauty of art religion; 3. Of the necessity of the oracle as leading to the concrete subjectivity of the dramatic actor.